ANALISIS TINGKAT KEPUASAN PENGGUNA TERHADAP TEKNOLOGI BARCODE DALAM APLIKASI MOBILE UNTUK BELANJA DI MINIMARKET - Aldino, Raja (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Abstract. The development of barcode technology in mobile applications has made shopping at convenience stores easier by enhancing the efficiency and speed of transactions. This study aims to analyze user satisfaction levels regarding barcode technology in mobile applications. The method used is a quantitative survey with the distribution of questionnaires to users who have utilized the barcode feature while shopping. The research results show that the majority of respondents are satisfied with the convenience and speed of transactions provided by barcode technology, although there are some issues such as device compatibility limitations and other technical problems. This study is expected to serve as a reference for application developers and convenience store managers in improving barcode-based services.